Hukum Sebagai Insrumen Untuk Mencapai Tujuan Negara serta Menggerakkan Perubahan terhadap Masyarakat - Deana Zahirah; Raina Nadheera (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Termination of employment often triggers industrial relations conflicts between workers and employers, conflicts between the two parties occur because of disputes over the amount of proper severance pay, long service pay, compensation money and so on. As stated in the Minister of Manpower Regulation number 14 of 2020 concerning guidelines for providing government assistance in the form of salary/wages subsidies, Article 1 paragraph (3) which states "salary/wages are the rights of workers/laborers who are received and expressed in the form of money as compensation from the employer or employer to workers/laborers who are determined and paid according to a work agreement, agreement or statutory regulations, including allowances for workers/laborers and their families for a work and/or service that has been performed” with the existence of statutory regulations life is organized and regulated justice and legal certainty are distributed, and crimes and violations are dealt with. (Jalaludin, 2011) The function of law is not only as a means of social control but to maintain public order, but also as an instrument to achieve state goals and drive changes in society towards what is desired, meaning law is the main means of presenting a welfare and public condition (Riwanto, 2017)